Non-high density lipoprotein cholesterol/high density lipoprotein cholesterol is L-shaped associated with all-cause mortality and U-shaped with cardiovascular mortality in hypertensive patients - Chen, Meiqian; Zhang, Li; Liu, Qian; Gu, Qingxin; Yu, Shuhui; Lu, Guanzhen (Frontiers in Endocrinology, 2025)
BackgroundPatients with hypertension may have better survival rates when their lipid metabolism is in balance. The relationship between the novel composite lipid metric, NHHR, and all-cause and cardiovascular mortality in hypertensive patients remains unknown and warrants further investigation.MethodsWe analyzed data from 5,561 hypertensive participants in the National Health and Nutrition Examination Survey (NHANES) spanning from 1999 to 2018. To determine the optimal NHHR cutoff point, we employed a maximum selection statistics approach. Participants were subsequently divided into groups for multivariate weighted Cox regression analysis. The association between NHHR and mortality risk was examined using restricted cubic splines (RCS). To investigate possible variations among different populations, subgroup analysis and interaction tests were carried out. The predictive capability of NHHR for survival outcomes was evaluated using time-dependent receiver operating characteristic (ROC) curves.ResultsOver a median follow-up period of 93 months, patients with hypertension exhibited an all-cause mortality rate of 21.78% and a cardiovascular mortality rate of 7.32%. A markedly elevated risk of cardiovascular death was associated with NHHR levels below 1.66 (HR 1.76; 95% CI 1.31-2.38; P < 0.001), as well as an increased risk of all-cause mortality (HR 1.58; 95% CI 1.31-1.91; P < 0.001). The RCS analysis revealed a U-shaped relationship with cardiovascular mortality (P = 0.0083) and an L-shaped correlation with all-cause mortality (P < 0.0001). Areas under the curve (AUC) for cardiovascular mortality were 0.97, 0.76, and 0.87, and for all-cause mortality were 0.76, 0.84, and 0.80 for the 3-year, 5-year, and 10-year survival periods.ConclusionsThe findings indicate that lower NHHR is associated with an increased risk of both cardiovascular and all-cause mortality, highlighting the critical need for comprehensive lipid management in the clinical management of hypertension. These results suggest that NHHR could serve as a valuable tool for identifying high-risk individuals for mortality, and should be incorporated into routine risk stratification assessments for hypertensive patients. This could more effectively improve patient prognosis and guide personalized treatment strategies.